A comparative study of daily interruption of sedation in surgical intensive care patients placed on mechanical ventilation (Latakia University Journal -Medical Sciences Series, 2025)
Introduction: Intensive care patients who require mechanical ventilation are often given an intravenous infusion of sedatives to treat anxiety and agitation and to facilitate their care. In many care units, sedatives are given by continuous intravenous infusion without stopping. This ensures a constant level of sedation and increases the patient’s comfort. However, this increases the duration of stay in intensive care and thus the duration of hospitalizationObjective: So came the idea of the study , daily stopping sedation and how it affect in reducing the duration of mechanical ventilation and thus the duration of stay in intensive care, which might improve rates of Survival of patients, and cause reduction in economic costs, and a reduction in the rate of complications that may occur from staying in ICU.Materials and methods: The study was conducted in the surgical Intensive Care Unit at Tishreen University Hospital - Latakia, for patients admitted for the year 2019-2020, who were placed on mechanical ventilation with intravenous sedation (Midazolam , Morphine) and who were undergoing treatment.For sedatives via continuous intravenous infusion, the study included 60 cases divided into two groups: the study group in which the intravenous sedatives were stopped daily, 24 hours after the start of sedation at a specific fixed time, and the control group in which the intravenous infusion of sedatives continued without an interruption.Results and Conclusion: In our study led to interruption Daily sedation shortens the duration of mechanical ventilation and the duration of stay in the care unit, which in turn leads to a reduction in the economic cost and a reduction in complications of mechanical ventilation.This procedure ensures the possibility of evaluating the patient by the medical staff, especially from a neurological perspective, and this in turn reduces additional investigations ( CT – MRI ... etc.)Thus, such as daily pausing, it is a safe and practical approach to managing mechanically ventilated patients, an approach that has therapeutic benefits for patients and an economic benefit for the medical facility.